Pendampingan Menjaga Kebersihan Melalui Program Kerja Visit To School Pada MIS Darul Muallaf Palangka Raya - Surawan, Surawan; Yanti, Febry (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Maintaining the cleanliness of the school environment is a very important aspect for school residents today. The Visit To School Program at MIS Darul Muallaf Palangka Raya can be used to develop this awareness, which is a community service initiative that aims to increase students' awareness and responsibility for the cleanliness of the school environment and develop their creativity. The method used in this service is service learning (SL) which provides students with the opportunity to learn through direct experience. This service involves collaboration between members of HMPS PAI IAIN Palangka Raya, teachers and students. The research results show positive changes in student attitudes, such as increasing environmental awareness, developing creativity, and increasing cooperation between students and related parties. This program has also succeeded in forming students' positive characters, such as responsibility, creativity and concern for the school environment.